Energy Saving Technologies and Practices in Facility Agriculture in Cold Regions - Ningning Li; Weiyao Xu; Yue Zhang; Wenchuan Ma; Yanjie Ren (Agronomy)
With the growth of the global population, energy demand continues to rise, making cross-regional energy transportation less viable as a sustainable solution. As a result, the construction of facilities for agriculture in cold regions has become increasingly important in the development of modern agriculture. However, cold region facility agriculture faces significant energy and environmental challenges, necessitating the advancement and application of energy saving technologies. This study addresses the high energy consumption in cold region facility agriculture by experimentally evaluating the integrated effects of geothermal heat pumps, solar collectors, intelligent light control systems, LED plant lamps, and smart ventilation systems in saving energy. The focus is on analyzing the technical adaptability and economic feasibility of these technologies under extremely cold conditions in Heilongjiang. The research findings indicate an overall energy saving rate of 17.8%, with energy savings in heating, lighting, and ventilation systems being 17.6%, 18.6%, and 17.4%, respectively. Economic analysis shows that geothermal heat pumps and high efficiency insulation materials have a short investment payback period and are suitable for widespread adoption, while solar collectors and intelligent light control systems are more appropriate for long-term application. This study demonstrates that intelligent and integrated energy saving technologies have significant potential in cold region facility agriculture, providing both data support and technical references for the efficient, low-carbon development of agriculture in cold climates. This study not only provides scientific evidence for the sustainable development of cold region facility agriculture but also highlights the practical implications of these technologies for reducing energy consumption and promoting low-carbon agriculture.